China - National Development and Sub-National Finance : A Review of Provincial Expenditures - World Bank (Washington, DC, 2013)
In China, the highly decentralized fiscal system undermines improvements in policy outcomes and contributes to increasing disparities among its regions. However, rather than re-centralizing, China would benefit from pursuing reforms to: improve expenditure and revenue assignments for the various levels of government; distribute fiscal resources more equally; and improve the use of these resources through better budget management at all levels of government. This report recommends a comprehensive reform effort that covers all the components of the inter-governmental fiscal system, arguing that selective interventions to address specific local financial problems such as defaults on pension and unemployment stipends, and payment arrears on teachers' salaries, have created some pervasive incentives. A piecemeal approach to inter-governmental fiscal reform is unlikely to succeed because it will not take into account the interdependence of transfers on revenue assignments or the role played by expenditure assignments on the adequacy of revenue assignments and transfers.